Insights into enhanced removal of Cd2+ from aqueous solutions by attapulgite supported sulfide-modified nanoscale zero-valent iron. (2nd December 2022) - Ren, Jun; Ma, Gui; Zhao, Weifan; Tao, Ling; Zhou, Yue; Liao, Caiyun; Tian, Xia; Wang, Huan; Meng, Kai; He, Yongjie; Dai, Liang
Abstract: The sulfidation of nanoscale zerovalent iron (nZVI) has received increasing attention for reducing the oxidizability of nZVI and improving its reactivity toward heavy metal ions. Here, a sulfide (S)-modified attapulgite (ATP)-supported nanoscale nZVI composite (S-nZVI@ATP) was rapidly synthesized under acidic conditions and used to alleviate Cd 2+ toxicity from an aqueous solution. The degree of oxidation of S-nZVI@ATP was less than that of nZVI@ATP, indicating that the sulfide modification significantly reduced the oxidation of nZVI. The optimal loading ratio was at an S-to-Fe molar ratio of 0.75, and the adsorption performance of S-nZVI@ATP for Cd 2+ was significantly improved compared with that of nZVI@ATP. The removal of Cd 2+ by S-nZVI@ATP was 100% when the adsorbent addition was 1 g/L, the solution was 30 mL, and the adsorption was performed at 25 °C for 24 h with an initial Cd 2+ concentration of 100 mg/L. Kinetics studies showed that the adsorption process of Cd followed the pseudo-second-order model, indicating that chemisorption was the dominant adsorption mechanism. The adsorption of Cd 2+ by S-nZVI @ATP is dominated by the complexation between the iron oxide or iron hydroxide shell of S-nZVI and Cd 2+ and the formation of Cd(OH)2 and CdS precipitates. HIGHLIGHTS: S-nZVI was loaded on ATP, effectively preventing nZVI agglomeration, and the sulfide modification significantly reduced the oxidation of nZVI. Cd 2+ removal was mailly attributed to complex with the iron oxides or iron hydroxide shell of S-nZVI. S-nZVI@ATP showed a stable adsorption effect on Cd 2+ over a wide pH range. The removal of Cd 2+ by S-nZVI@ATP follows the quasi-second-order kinetic adsorption model. Graphical Abstract